FPGA-based implementation of a Gaussian smoothing filterwith powers-of-two coefficients - Ivashko, Andrey; Zuev, Andrey; Karaman, Dmytro; Moškon, Miha (Національний технічний університет "Харківський політехнічний інститут", 2024)
The purpose of the studyis to develop methods for synthesizing a Gaussian filter that ensures simplified hardware and software implementation, particularly filters with powers-of-two coefficients. Such filters can provide effective denoising of images, including landscape maps, both natural and synthetically generated. The study also involves analyzing of methods for FPGA implementation, comparing their hardware complexity, performance, and noise reduction with traditional Gaussian filters. Results. An algorithm for rounding filter coefficients to powers of two, providing optimal approximation of the constructed filter to the original, is presented, along with examples of developed filters. Topics covered include FPGA implementation, based on the Xilinx Artix-7 FPGA. Filter structures, testing methods, simulation results, and verification of the scheme are discussed. Examples of the technological placement of the implemented scheme on the FPGA chip are provided. Comparative evaluations of FPGA resources and performance for proposedand traditional Gaussian filters are carried out. Digital modeling of the filters and noise reduction estimates for noisy images of the terrain surface are presented. The developed algorithm provides approximation of Gaussian filter coefficients as powersof two for a given window size and maximum number of bits with a relative error of no more than 0.18. Implementing the proposed filters on FPGA results in a hardware costs reduction with comparable performance. Computer simulation show that Gaussian filters both traditional and proposed effectively suppress additive white noise in images. Proposed filters improve the signal-to-noise ratio within 5-10 dB and practically match the filtering quality of traditional Gaussian filters.

Метою дослідженняє розробка методів синтезу гаусівського фільтра, якігарантуютьспрощену апаратну та програмну реалізацію, зокрема фільтрів з коефіцієнтами, що є степенями двійки. Такі фільтри можуть забезпечувати ефективне приглушення шумів на зображеннях, включаючи ландшафтні карти, як природні, так і синтетично створені. Дослідження також включає аналіз методів реалізації на FPGA, порівняння апаратної складностірезультатів їх роботи, продуктивності та приглушення шумів у порівнянні зтрадиційними гаусівськими фільтрами. Представлений алгоритм округлення коефіцієнтів фільтра до степенів двійки, що забезпечує оптимальне наближення побудованого фільтра до оригіналу, разом з прикладами розроблених фільтрів. Розглянуті теми включаютьпрактичнуреалізацію на основі FPGA Xilinx Artix-7. Обговорюються структури фільтрів, методи тестування, результати симуляції та верифікація схеми. Надані приклади технологічного розміщення реалізованої схеми на чіпі FPGA. Проведені порівняльні оцінки ресурсів та продуктивності FPGA для запропонованих та традиційних гаусівських фільтрів. Представлені цифрові моделі фільтрів та оцінки зменшення шумів для зашумлених зображень поверхні місцевості. Розроблений алгоритм забезпечує наближення коефіцієнтів гаусівського фільтра у вигляді чисел ступенюдвійки для заданого розміру вікна та максимальної кількості бітів з відносною похибкою не більше 0,18. Реалізація запропонованих фільтрів на FPGA призводить до зменшення витрат на апаратне забезпечення з порівняною продуктивністю. Комп'ютерне моделювання показує, що як традиційні, так і запропоновані гаусівські фільтри ефективно приглушують адитивний білий шум на зображеннях. Запропоновані фільтри покращують співвідношення сигнал/шум на 5-10 дБ та практично відповідають якості фільтрації традиційних гаусівських фільтрів.
Реалізація зглаждуючого фільтру Гаусаз коефіцієнтами ступенів двох на основі FPGA
Keywords: noise filtering; hardware implementation; simulation training complex; performance; filtering quality; scheme; апаратна реалізація; продуктивність; генерація ландшафту; оцінка якості; комп'ютерне моделювання